Altered Reward Reactivity as a Behavioural Endophenotype in Eating Disorders: A Pilot Investigation in Twins. (May 2017) - Kanakam, Natalie; Krug, Isabel; Collier, David; Treasure, Janet
Abstract: Altered reward reactivity is a potential risk endophenotype for eating disorders (EDs). The aim of this study was to examine reward reactivity in female twins with EDs and compare it with a twin control group. A sample of 112 twins [ n = 51 met lifetime DSM‐IV ED criteria (anorexia nervosa n = 26; bulimic disorders n = 24), n = 19 unaffected cotwins and n = 42 control twins] was administered measures assessing reward reactivity, including the Game of Dice Task, the Behavioural Inhibition/Activation (BIS/BAS) Scales and the Appetitive Motivation Scale (AMS). Within pair, correlations for monozygotic and dizygotic twins were calculated and generalised estimating equations compared probands with non‐ED cotwins and controls. The BAS and the AMS were reduced in EDs and negatively associated with restrictive symptoms. In addition, monozygotic twins pairs demonstrated significant within pair similarity for the BAS and AMS. Conversely, there was less evidence to support the BIS or risky decision‐making as measured by the Game of Dice Task as an endophenotype in EDs. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.